Towards a Comprehensive Understanding of Hadith Sciences: Al-Gumari’s Reconstruction of Riwayah and Dirayah - Assagaf, Ja'far; Wahid, Abd (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The two primary branches of hadith sciences, riwayah (transmission) and dirayah (critical analysis), were historically considered conclusive by scholars following the 10th century AH, according to the definition given by al-Suyuti. However, this point of view encountered considerable criticism from al-Gumari. This study examines al-Gumari's epistemological methodology for reconstructing hadith sciences, employing John Dewey's reconstruction theory and Taqi Yazdi's comparative theory as analytical frameworks. The findings indicate substantial differences between al-Gumari and other scholars regarding their conceptualisation of the hadith sciences of riwayah and dirayah. The differences manifest in the domains of terminology, linguistic considerations, illustrative examples, and the practical application of these two branches of hadith sciences. Al-Gumari added the categories of sahih (authentic), hasan (good), and da‘if (weak) hadith to the definition of riwayah so that it included both theoretical and practical aspects. In the domain of dirayah, he incorporated components such as linguistic analysis, matan (content) criticism, principles of usul al-fiqh (the principles of jurisprudence), and fiqh (jurisprudence), extending beyond the boundaries traditionally confined to usul al-hadith (principles of hadith). Still, there are some areas where both schools agree, especially when it comes to the sciences of gharib al-hadith (rare or unfamiliar words in hadith) and asbab wurud al-hadith (specific circumstances of revealing hadith), which can be put in either riwayah or dirayah depending on the situation. Through al-Gumari’s reconstructive efforts, a more expansive framework for dirayah emerges, integrating specialised studies in linguistics, matan analysis, and jurisprudence. This method significantly enhances the interpretive scope of hadith sciences, fostering a more comprehensive understanding of its theoretical and practical aspects.